Long-term response of over ten years with sorafenib monotherapy in metastatic renal cell carcinoma: a case report. (December 2016) - Ueda, Kosuke; Suekane, Shigetaka; Ogasawara, Naoyuki; Chikui, Katsuaki; Suyama, Shunsuke; Nakiri, Makoto; Nishihara, Kiyoaki; Matsuo, Mitsunori; Igawa, Tsukasa
Abstract Background Molecular targeted therapies have dramatically improved the prognosis of metastatic renal cell carcinoma. However, patients in whom the treatment could initially be effective will experience disease progression later. Case presentation A 74-year-old Japanese man who was diagnosed with renal cell carcinoma with no evidence of metastasis presented to our hospital. He initially underwent radical nephrectomy, and subsequently the disease metastasized to the lung. Sorafenib was started for the lung metastases 1 year after the operation. The dose of sorafenib was reduced and temporarily discontinued because adverse events, including fatigue and cardiac infarction, occurred. The patient has continued sorafenib monotherapy for over 10 years without disease progression and severe adverse events. Conclusions We present a rare case of a patient with metastatic renal cell carcinoma who has survived for over 10 years while receiving sorafenib monotherapy.